Role of myeloperoxidase in atrial fibrillation and ischemic heart disease - G. F. Bunenkova; S. P. Salikova; V. B. Grinevich; E. S. Ivanyuk (Klinicist)
Atrial fibrillation and ischemic heart disease are the key problems in cardiology. Despite of numerous clinical trials and researches underlying molecular biology remains uncertain. Atrial fibrillation and ischemic heart disease are often combined. During ischemic heart disease progression myocardial tissue structure are changing which lead to structural and electrophysiological remodeling and promote atrial fibrillation. It has been shown a crucial role of oxidative stress and chronic systemic inflammation in ischemic heart disease and atrial fibrillation. Myeloperoxidase (MPO) is one of marker of oxidative stress and inflammation that located in azurophilic granules of neutrophils and monocytes. There are a numerous articles showed a relation between MPO level and cardiovascular disease. MPO is a peroxidase enzyme that is important part of immune system. During disease MPO could facilitate chronic inflammation and local tissue damage through active oxygen forms. MPO releases after lysosome conjunction with phagosome. Oxygen reductase activity of MPO lead synthesis of hypochlorous acid that play role not only in organism protection from infection agents but in matrix transformation and fibrosis. It has been shown MPO can destabilize atherosclerotic plaque and modifies low- and high-density lipoproteins that promote atherosclerosis and ischemic heart diseaseу progression. This review summarizes current data about role of MPO in atrial fibrillation and ischemic heart disease pathogenesis.